Needs As The Dominant Factor of Generation Z in Telemental Health (TMH) Services Utilization - Alifa, Ariska Widya; Suryawati, Chriswardani; Wigati, Putri Asmita (jitek, 2023)
Nowadays, mental health is still an unfinished problem in Indonesia. Telemental health (TMH) exists as a form of adaptation toward technological developments that are expected to help address challenges in mental health services. There is a continuous increase in the number of Generation Z who suffer mental health problems. Meanwhile, the coverage of mental health services is still low even though the convenience of TMH has supported it. This study aims to analyse the factors that influence the utilisation of TMH among Generation Z based on Andersen's theory. This quantitative research collected 180 respondents and then analysed them using univariate, bivariate, and multivariate. Results showed a relationship between the needs factor, access to TMH, health worker support, and residence on the use of TMH. While the variables that aren't related are gender, education, occupation, marital status, and knowledge. The needs factor dominates the effect of using TMH among Generation Z in Indonesia, where a change in it can affect 15 times the utilisation of TMH. To develop TMH into sustainable services, providers can create the right strategy. It’s recommended to Generation Z to avoid self-diagnosis accompanied by enriching knowledge about maintaining mental health.